Fragmentation of the dorsal distal aspect of the talus on weanling survey and pre‐sale radiographs of juvenile Thoroughbreds: prevalence and 2‐ and 3‐year‐olds racing performance. Issue 3 (17th February 2019) - Steel, CM; Devery, S; Hance, SR; Adkins, AR; Hitchens, PL
Abstract : Background: Fragmentation of the dorsal aspect of the distal talus (FDDT), at the dorsolateral articular margin of the proximal intertarsal joint (PITJ) on pre‐sale radiographs of yearling Thoroughbreds has not been previously described and data to support decisions made by veterinarians to predict future racing potential of horses with these lesions are lacking. Methods: In this retrospective case–control study we aimed to determine the prevalence of FDDT in juvenile Thoroughbreds and to report their race records. From a database of survey and repository radiographic examinations of 5709 horses, 36 with FDDT were identified. Results: The prevalence of FDDT was 0.63% (36/5709; 95%CI 0.44, 0.87), compared with 5.01% (286/5709; 95%CI 4.46, 5.61) for osteochondrosis of the distal intermediate ridge of the tibia in the same population. In most cases, a single oval‐shaped fragment 1–12 mm in diameter was present. When comparing cases with matched controls, there were no significant differences in mean sale price, whether horses started in a trial or race and mean number of starts, wins, places and prize money when 2‐ and 3‐years old. Conclusion: FDDT did not appear to affect racing performance, although a larger‐scale study is warranted to confirm this finding.